Book Review: “Ritual Melodies of Ukrainians in the Context of Slavic-Baltic Early Traditional Melodic Areal” By Iryna Klymenko - Panchenko, Alexander (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2023)
Book Review: “Ritual Melodies of Ukrainians in the Context of Slavic-Baltic Early Traditional Melodic Areal” By Iryna Klymenko